Crompton's Campaign The Professionalisation of Dance Pedagogy in Late Victorian England - Buckland, Theresa Jill (Edinburgh: Edinburgh University Press, 2007)
RESUMEN: In late Victorian England, dance teachers lacked national representation and means of communication among themselves to address professional concerns. By 1930, at least ten professional associations had emerged in Britain, some of which, such as the Royal Academy of Dance (RAD), The British Association of Teachers and Dancing (BATD) and the Imperial Society of Teachers of Dancing (ISTD), are still active today. Little has been written about the wider context of their foundation and of earlier initiatives to establish a professional body for dance pedagogy in England. A key figure in contemporaneous efforts to develop an infrastructure was Robert Morris Crompton (c.1845-1926), a London-based dancing master. Choreographer, writer, and founder-editor of the first periodical devoted to dance in England (Dancing, 1891-1893), Robert Crompton finally succeeded in establishing a national organisation that was devoted to both social and stage dancing in 1904. As the first president of the ISTD, his visionary ideals of an annual technical congress, improvements in the status of the profession, and the future enhancement of dance as an art were placed on a firm institutional footing. Charlatan practitioners, declining standards in the ballroom, and unhelpful licensing laws, together with a scattered and highly individualised competitive profession, were challenges in the early 1890s that Crompton initially failed to overcome. Records of his dreams and anxieties in Dancing provide valuable insight into the problems that beset the teachers of the time. In tandem with other source material relating to the social context for dance of the period, consideration of the trials and aspirations that lay behind Crompton's campaign for a national professional association help to broaden understanding of the place of dance in late Victorian society in England.